1998
DOI: 10.1099/00221287-144-2-433
|View full text |Cite
|
Sign up to set email alerts
|

Organization around the dnaA gene of Streptococcus pneumoniae

Abstract: The dnaA gene region of Streptococcus pneumoniae was cloned and sequenced. A tRNA gene, seven ORFs and three DnaA box clusters were identified. The order of the genes and intergene regions found was tRNAhgorfl-DnaA box cluster 3-htrA-spoOJ-DnaA box cluster 2-dnaA-DnaA box cluster l-dnaN-orfX-orfY. Five ORFs are homologous to known bacterial genes. The tRNAhg gene and orfl, also called orfL, have already been described in pneumococci and have been reported to be preceded by the competence regulation locus comCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Although the downstream gene spoJ would appear to be the most likely candidate for this role, our preliminary experiments have not shown that the deletion of spoJ either affects competence in a wild-type background or restores competence to a CiaH-activated strain (data not shown). While we cannot exclude the possibility that spoJ may affect the development of competence under other conditions not tested, it is also notable that the htrA-spoJ locus lies adjacent to the putative origin of replication of the pneumococcal chromosome (16,21,54). A polar effect related to the initiation of DNA replication, similar to that suggested by Claverys et al (8), might be postulated to result from changes in transcriptional activity in this region.…”
Section: Discussionmentioning
confidence: 65%
“…Although the downstream gene spoJ would appear to be the most likely candidate for this role, our preliminary experiments have not shown that the deletion of spoJ either affects competence in a wild-type background or restores competence to a CiaH-activated strain (data not shown). While we cannot exclude the possibility that spoJ may affect the development of competence under other conditions not tested, it is also notable that the htrA-spoJ locus lies adjacent to the putative origin of replication of the pneumococcal chromosome (16,21,54). A polar effect related to the initiation of DNA replication, similar to that suggested by Claverys et al (8), might be postulated to result from changes in transcriptional activity in this region.…”
Section: Discussionmentioning
confidence: 65%
“…As was shown to be the case for htrA of S. pneumoniae (12,47) and S. pyogenes (11,28), htrA of S. mutans is near the apparent origin of chromosome replication. Immediately downstream of htrA, genes homologous to spo0J and dnaA were identified.…”
Section: Discussionmentioning
confidence: 71%
“…DnaA boxes, which are bound by DnaA proteins to form the initiation complex for chromosome replication were identified in this region. Similar to those of S. pneumoniae (12) and S. pyogenes (28), the DnaA boxes of S. mutans are localized to untranslated regions upstream of htrA and upstream and downstream of dnaA (Fig. 1).…”
Section: Discussionmentioning
confidence: 76%
“…The genomic origin of replication has not been experimentally identified in S. pneumoniae; however, based on the presence of clusters of DnaA boxes and other genomic features, we hypothesize that the S. pneumoniae origin of DNA replication is upstream of dnaA, which is gene spr0001 in our nomenclature system (16).…”
Section: Resultsmentioning
confidence: 97%